Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics